Microscopic colitis: can it be qualitatively and quantitatively characterized? - Fasoli, R; Talbot, I; Reid, M; Prince, C; Jewell, D (1992)
This study reports the histological features helpful in diagnosing microscopic colitis. Rectal biopsy specimens from 14 patients with microscopic colitis, 14 with active ulcerative colitis and 14 without colonic inflammation were pooled and then assessed by three observers according to a predetermined protocol. Inter-observer agreement was good except for Paneth cell metaplasia and endocrine cell metaplasia. Compared with healthy tissue, microscopic colitis showed a significant (p less than 0.05) increase in chronic inflammatory cells and a depletion of goblet cells but these changes were less pronounced than those seen in ulcerative colitis (p less than 0.05). In contrast to ulcerative colitis, microscopic colitis was associated with a more marked infiltration with eosinophils and an increase in intra-epithelial lymphocytes. These results show that microscopic colitis can be distinguished both from normal colonic tissue and from ulcerative colitis.